Resiliência familiar em tempos pandêmicos: relações entre irmãos de crianças com transtorno do espectro autista e seus elementos fundamentais. - Oliveira, Jade Maria Albuquerque de (2024)
This research is a segment of the study with the theme "Resilience of Families of Children with Special Needs in the Context of the COVID-19 Pandemic." It is noteworthy that the research is funded by the Call CNPq/MCTI/FNDCT No. 18/2021 - UNIVERSAL. This study aimed to analyze the fundamental elements of family resilience expressed in the reports of siblings of autistic children during the COVID-19 pandemic. The theoretical framework adopted for this study was Froma Walsh (2016). This is a descriptive study with a qualitative approach, conducted between March 2022 and June 2024. The research setting was a WhatsApp group of mothers of autistic children from the city of Sobral. The participants in this research comprised neurotypical siblings of children with Autism Spectrum Disorder. A flyer about the research was created and sent to the WhatsApp group of the mothers, inviting their neurotypical children to participate in the study. Responses were obtained from 22 mothers, of which 8 children did not agree to participate, resulting in responses from 14 neurotypical children. The meeting took place online via the Google Meet platform, and the questions posed to the interviewees followed a semi-structured script to guide the interviewer. The analysis and transcription of the statements were conducted using the content analysis method (CA) of Bardin's framework through thematic analysis. From the obtained responses, 273 recording units were registered, which were organized into 17 categories and 27 subcategories based on the fundamental elements of the key processes in Froma Walsh's theoretical framework. This research was submitted for approval by the Research Ethics Committee of the Health Sciences Sector of the Federal University of Paraná, under opinion No. 5.920.457, and followed the guidelines of Resolution No. 466/12 of the National Health Council. The siblings' statements were organized into three major thematic classes: Belief System, Organizational Patterns, and Communication/Problem-Solving. Upon analyzing the interviews, of Walsh's nine (9) fundamental elements of resilience, six (6) fundamental elements were identified in the study: 1. Finding meaning in adversity; 2. Positive outlook; 4. Flexibility; 5. Connectedness; 6. Social and economic resources; 7. Clear and consistent messages; and 8. Open emotional expression. The results of the analysis of these key processes highlight the neurotypical siblings' understanding, their search for meaning, their future vision with their sibling with ASD, flexibility concerning routine, leadership, and activities carried out. It also emphasizes the role of the family in supporting difficulties and disseminating knowledge, which often manifests in an ableist and prejudiced perspective. The siblings expressed positive feelings towards their autistic siblings, and family leisure activities with their siblings were highlighted as positive for them. The siblings also expressed a need for moments of privacy. This research will contribute to families and society by helping them understand and perceive the needs of neurotypical siblings of children with ASD, recognizing that these neurotypical siblings often feel overwhelmed. This study concludes that all siblings are resilient in the fundamental elements discussed, whether or not they achieve the key processes of the fundamental elements of resilience. However, these siblings are capable of reinterpreting their lives, daily routines, and relationships in the context of challenges.